Parents' information needs, treatment concerns, and psychological well-being when their child is diagnosed with adolescent idiopathic scoliosis: A systematic review. Issue 6 (June 2021) - Motyer, Gillian; Dooley, Barbara; Kiely, Patrick; Fitzgerald, Amanda
Highlights: This is the first systematic review of parents' experiences of adolescent idiopathic scoliosis. Meeting parents' information needs about their child's scoliosis treatment is important. Surgical complications, pain, and fulfilling the parenting role are main concerns for parents. Parents experience heightened anxiety at their child's scoliosis diagnosis and surgery. Further research into parents' support needs related to their child's scoliosis is required. Abstract: Objective: We systematically reviewed the experiences of parents who have a child with adolescent idiopathic scoliosis in order to understand their needs and concerns related to their child's healthcare, and assist health professionals in supporting parents of this paediatric patient group. Methods: A systematic search strategy identified eighteen relevant studies published between 2000 and 2020. Quality was assessed using the Mixed Methods Appraisal Tool and the literature was narratively synthesised. Results: Three main themes were evident across the literature including information needs, treatment concerns, and psychological well-being. Studies predominantly focused on the surgical treatment of scoliosis. Conclusion: Parents face challenges such as acquiring appropriate knowledge about scoliosis to participate in healthcare decisions and coping with their child undergoing invasive spinal surgery. Throughout this time, their psychological well-being can be negatively impacted. Considering parents' experiences and support needs throughout this anxiety-provoking time is an important step in delivering family-centered care and promoting better outcomes for paediatric patients. Practice Implications: Providing parents with appropriate resources and addressing concerns around surgical complications, postoperative pain, and how they can best support their child before and after surgery, may alleviate some of the emotional burden that parents experience.